Consumer's Negative emotions, Financial Decisions, Financial Advice - Konstantaki, Violetta (2007)
Abstract The purpose of this study is to explore the consumers decision making process. In particular, this study attempts to examine consumers negative emotions, which elicit during a decision processing. Especially, the case of a financial decision will be examined. Moreover, consumers negative emotion will be investigated in relation with consumers coping behaviour. To be more specific, the option of seeking advice as a successful consumers coping behaviour will be explored. Additionally, the option of seeking advice will be further analysed in terms of advice by the social environment and the advice by a professional. The current study attempts to cast light on a specific target group of elderly financial customers. It should be mentioned that this study is supported by literature related to consumer rational theories, their critics and financial services marketing articles. The most appropriate research method, which the research question is better answered, is the experimental approach. Especially, a research method will use the scenario based on the experiment. It can be argued that the studies results are demonstrating particular academic and managerial implications. It was concluded that the advice option is a successful coping behaviour for consumers negative emotions. Hence, it can be stated that the financial advice for the consumer is of vital importance, as consumers are experiencing significantly lower levels of negative emotions when they are able to seek an advice. On the other hand, in the research not significant was found difference in the consumers negative emotions when they have to select between a professional or non- a professional advice. As a result, the financial institutions could take the advantage of this research's outcomes. As the research results demonstrate, the advice which is offered to the consumers could lead to increasing the number of sales in the financial services. Consumers not only experience lower levels of negative emotions, but are also more motivated to take a financial decision. Moreover, financial products turn out to be a long term decision, therefore relationship marketing could be successfully applied in the financial service sector. Finally, it could be argued that consumers using the advice option could be more satisfied, customers as consumer emotions are closely related with customer satisfaction.